COVID-19 TestNorm: A tool to normalize COVID-19 testing names to LOINC codes. (13th August 2020) - Dong, Xiao; Li, Jianfu; Soysal, Ekin; Bian, Jiang; DuVall, Scott L; Hanchrow, Elizabeth; Liu, Hongfang; Lynch, Kristine E; Matheny, Michael; Natarajan, Karthik; Ohno-Machado, Lucila; Pakhomov, Serguei; et al.
Abstract: Large observational data networks that leverage routine clinical practice data in electronic health records (EHRs) are critical resources for research on coronavirus disease 2019 (COVID-19). Data normalization is a key challenge for the secondary use of EHRs for COVID-19 research across institutions. In this study, we addressed the challenge of automating the normalization of COVID-19 diagnostic tests, which are critical data elements, but for which controlled terminology terms were published after clinical implementation. We developed a simple but effective rule-based tool called COVID-19 TestNorm to automatically normalize local COVID-19 testing names to standard LOINC (Logical Observation Identifiers Names and Codes) codes. COVID-19 TestNorm was developed and evaluated using 568 test names collected from 8 healthcare systems. Our results show that it could achieve an accuracy of 97.4% on an independent test set. COVID-19 TestNorm is available as an open-source package for developers and as an online Web application for end users (https://clamp.uth.edu/covid/loinc.php ). We believe that it will be a useful tool to support secondary use of EHRs for research on COVID-19.